Deliberation and Automaticity in Habitual Acts - Douskos, Christos (ETHICS IN PROGRESS, 2018)
Most philosophers and psychologists assume that habitual acts do not ensue from deliberation, but are direct responses to the circumstances: habit essentially involves a variety of automaticity. My objective in this paper is to show that this view is unduly restrictive. A habit can explain an act in various ways. Pointing to the operation of automaticity is only one of them. I draw attention to the fact that acquired automaticity is one outgrowth of habituation that is relevant to explanation, but not the only one. Habituation shapes our emotional and motivational make up in ways that affect deliberation itself. Hence mentioning a habit might be indispensable in explaining an act which nevertheless ensues from deliberation. The view that habitual acts are direct responses to the circumstances implies an impoverished conception of habit, which fails to do justice to its rich explanatory potential in theoretical and pre-theoretical contexts, as well as to its role in the history of philosophy.